Paul Ariste ja vepsa rahvaluule - Kristi Salve (Eesti Kirjandusmuuseum, 2003)
Though Paul Ariste had extensive knowledge of different living, extinct and artificial languages, he has always regarded his mother tongue, the Estonian language, the most beautiful language in the world. He managed to instil this conviction also into his students, both Estonian and of other, mostly Finno-Ugric, origin. The Vepsian folklore and language remained in the periphery of Paul Ariste's research subjects: his serious interest in the language and cultures may have prompted his inclination towards the non-Estonian folklore while working at the Estonian Folklore Archives. On his initiative, although by the consent of Oskar Loorits, PhD and the first head of the Estonian Folklore Archives, separate collections were established on the folklore material of the ethnic minorities then living in Estonia and of other peoples, mostly the Balto-Finns. A smaller collection (ERA, Mitmesugused rahvad) also includes material on the Vepsian folklore. Paul Ariste was once asked to collect sayings related to breaking a tooth from as many ethnic groups as possible. This work resulted in his first records on the Vepsian folklore. A few years later, while leading the field work expeditions of the students of the Tartu University in 1953, 1954, 1955 and 1961, P. Ariste's work on recording the Vepsian folklore expanded. Material collected on these expeditions, constituting more than 400 pages, was contributed to the collection of the then Chair of Finno-Ugric Languages and were destroyed in the 1965 fire at the main building of the University of Tartu. Fortunately, a small part of the collection made its way to the Estonian Literary Museum, and is preserved in the catalogue RKM, Soome-ugri 2, containing mostly folk songs from the central Vepsia, but also folk tales. P. Ariste has also published some of the Vepsian folk tales he collected ("Vepsa muinasjutte" [The Folk Tales of the Veps], Tallinn 1964). This was also his only publication solely on the Vepsian material. The Folk Tales of the Veps contains six tales with a ...